Investigating the Relationship between Symptoms of Histrionic Personality Disorder and Experiences of Child Abuse among Students of Tabriz Islamic Azad University - Derakhshi, Shirin Mohammadi (Journal of History Culture and Art Research, 2017)
The present study attempts to investigate the relationship between symptoms of histrionic personality disorder and experiences of child abuse among students of Tabriz Islamic Azad University in 2013-2014. The general aim of this study is to predict histrionic personality disorder in adulthood based on child abuse experiences during childhood. The population of this study include 19599 people among whom 377 were selected through simple random sampling. The instrument of this study includes Millon-3 CASRS questionnaire and child abuse questionnaire. The data was analyzed by Pearson correlation coefficient and multiple regression. The obtained results revealed that there is significant relationship between histrionic personality disorder (independent variable) and dimensions of child abuse (dependent variable) that includes emotional, neglect, physical, and sexual child abuse. Considering different dimensions of child abuse, neglect of child and sexual child abuse have the most and the least contribution in predicting symptoms of histrionic personality disorder in adulthood. In addition, the results showed that all four dimensions of child abuse can predict symptoms of histrionic personality disorder in adulthood, but ignorance or neglecting child has the most effect and sexual dimension has the least effect in the prediction.